Effects of CYP2C19 genetic polymorphisms on the cure rates of H. pylori in patients treated with the proton pump inhibitors: An updated meta-analysis - Zhao, Xianghong; Zhang, Zhongqiu; Lu, Fang; Xiong, Mengqiu; Jiang, Liping; Tang, Ke; Fu, Min; Wu, Yu; He, Bangshun (Frontiers in Pharmacology, 2022)
Background: The CYP2C19 genetic polymorphisms could affect the eradication rate of Helicobacter pylori (H. pylori); however, the conclusion was still not definite due to diverse study designs. The main purpose of this study is to confirm the effects of CYP2C19 genetic polymorphisms on H. pylori eradication rate according to stratified analysis. Materials and Methods: The literature was searched with the key words "H. pylori" and "CYP2C19" in CNKI and PubMed up to October 31th, 2021, and the studies were limited to clinical observational or randomized controlled trials (RCTs). The pooled results were used to assess the effects of CYP2C19 genetic polymorphisms on H. pylori eradication rate. Results: Eradication rates were significantly different between genotype of homozygous extensive metabolizers (EM) and poor metabolizers (PM) (OR = 0.70, 95% CI: 0.51 ~ 0.95), and between homozygous extensive metabolizers (EM) and heterozygous extensive metabolizers (IM) (OR = 0.71, 95% CI: 0.59 ~ 0.86), but not between IM and PM. Meanwhile, there was a significantly lower H. pylori eradication in EM subjects than in PM subjects when treated with omeprazole (65.9% vs. 88.8%), lansoprazole (73.7% vs. 82.6%), or esomeprazole (80.9% vs. 87.9%), but not rabeprazole or pantoprazole. In addition, there was a significantly lower H. pylori eradication in EM subjects than in PM subjects when treated with the proton pump inhibitors (PPIs) for 7 days (76.3% vs. 83.8%), but not 14 days (85.0% vs. 90.2%). Conclusions: Carriers of CYP2C19 loss-of-function variant alleles (IM and PM) exhibit a significantly greater eradication rate of H. pylori than noncarriers (EM) only when treated with omeprazole (84.4% vs. 65.9%), esomeprazole (84.6% vs. 80.0%), or lansoprazole (83.2% vs. 73.7%), moreover, the same is true in therapy of 7 days (76.3% vs. 82.1%) and Asian populations (78.9% vs. 82.5%).